Structured literature review of published research on indirect translation (2017-2022) - Pięta Hanna; Ivaska Laura; Gambier Yves (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Drawing on a structured literature review, this article offers a meta-analysis of published research on indirect translation in different domains between 2017 and 2022. The article first presents the rationale and method used in designing and implementing bibliographic searches, as well as in examining selected publications. It then presents the findings of the structured literature review, focusing on the date of selected publications, their authorship, translation domains and research approaches. The results show a significant increase in publications on indirect translation, with much more co-authored papers and a slight move towards author specialisation in this field. Our findings also show that literature is still the prevalent domain, and empirical studies prevail, particularly those that are product-oriented and look at the quality of indirect translations. Process-oriented, participant- oriented and context-oriented studies are still a minority, and they mainly emerge from research on non-literary texts. The article also includes a compilation of references to publications analysed as part of the literature review. A dataset resulting from this meta-analysis is shared in open access to ensure replicability. We hope that this meta-analysis will help highlight recent developments and blind spots, serving as useful tools for researchers wanting to diversify perspectives in indirect (literary) translation.